Motivation and Career Development: Is Mentoring Function issue? - Rita Wahidi, Kemala; Sukma Kamaratri, Nuning; Wekadigunawan, CSP; Roespinoedji, Djoko (International Journal of Psychosocial Rehabilitation, 2020)
The issue of achieving optimal employee performance in a hospital is related to achieving comprehensive hospital performance targets. This is important as a signal to hospitals if they want sustainability so that employee performance must continue to be good. Thus, professional management needs support in mentoring activities, to increase employee motivation and career development in order to produce good nurse performance. The purpose of this study was to obtain empirical evidence of the influence of the functions of mentoring, motivation and career development on nurse performance in health institution. This study uses a survey research method with an explanatory approach to causality research. The unit of analysis is nurse. Time horizon uses cross section. The sampling technique is saturated sampling. This study uses Path Analysis, the number of samples successfully collected was 148. Data analysis using path analysis with statistical analysis.The results showed that the functions of mentoring, motivation and career development jointly influenced the performance of hospital nurses; the mentoring function has a significant positive effect on nurse motivation variables; the mentoring function does not have a significant positive effect on nurse career development variables; the mentoring function has a significant positive effect on nurse performance variables; career development has a significant positive effect on nurse performance variables; and nurse motivation has a significant positive effect on nurse performance variables.Research findings are that hospital nurses have a high internal or intrinsic drive to make themselves have high expertise, high competence, experience, skills and high skills through training in order to meet professional qualification standards according to expertise and competence.